2020
DOI: 10.18502/kss.v4i7.6845
|View full text |Cite
|
Sign up to set email alerts
|

Blended Learning for Augmented Reality to Increase Student Competitiveness the Filling Subject Toward Making Indonesia 4.0

Abstract: Human resource development can be done by various step such as improvement of quality education especially model and learning methode.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 0 publications
0
7
0
1
Order By: Relevance
“…At the beginning of 2022, along with the decline in active cases of Covid-19, the learning process was gradually carried out face-to-face. Blended learning is becoming popular to be implemented in the implementation of learning in various countries including Indonesia (Arifin, 2020;Kusdiyanti et al, 2020). Blended Learning is a mixed learning process between face-to-face learning in the classroom and online learning (Jaya Saragih et al, 2020;Subandowo et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…At the beginning of 2022, along with the decline in active cases of Covid-19, the learning process was gradually carried out face-to-face. Blended learning is becoming popular to be implemented in the implementation of learning in various countries including Indonesia (Arifin, 2020;Kusdiyanti et al, 2020). Blended Learning is a mixed learning process between face-to-face learning in the classroom and online learning (Jaya Saragih et al, 2020;Subandowo et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The results of field trials showed that the percentage of student response questionnaire analysis results was 94% in the very good category. It can be concluded that the learning process will be more effective and make it easier for students to learn abstract material by using the 7 Wonders of the World-APP Augmented Reality-based media as social studies learning media in elementary schools (Celik et al, 2020;Habig, 2020;Kusdiyanti et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…MZ et al, 2021;Peterson et al, 2020). By looking at students' cognitive development, the development of Augmented Reality-based media will be preferred by students in understanding abstract concepts in the learning process (Alkhattabi, 2017;Flores-Amado et al, 2020;Kusdiyanti et al, 2020). Augmented Reality is a technology whose effectiveness can be seen significantly in the field of education.…”
Section: Introductionmentioning
confidence: 99%
“…Selain itu, blended learning sangat mendukung pendidikan di era 4.0 (Hartono et al, 2018). Sebagai solusi dalam mengatasi permasalahan pembelajaran dimasa pandemi , blended learning merupakan pendekatan pembelajaran metodologis yang menghubungkan beberapa pendekatan berbasis Asyn-choronous Learning Network atau metode pembelajaran melalui pembelajaran internet (Kusdiyanti et al, 2020). Sehingga dalam penerapannya media pembelajaran online dalam Learning Management System (LMS) didesain ulang dengan memadukan sistem online dan tatap muka di kelas untuk menciptakan kegiatan pembelajaran yang mandiri, aktif, efektif dan efisien, pemanfaatan blended learning sebagai media pembelajaran kompetensi dasar vokasi dengan menggunakan Model blended learning memiliki efektivitas internal dan eksternal yang mampu meningkatkan keterampilan pemahaman atau pembelajaran teoritis bagi siswa (Kusdiyanti et al, 2020).…”
Section: Pendahuluanunclassified